Studi pada Wali Murid di Kota Magelang Provinsi Jawa Tengah: Faktor yang Berhubungan dengan Penolakan Imunisasi Measles Rubella - Zulfa Fatmawati Dwi Asdika; Martini Martini; Dwi Sutiningsih; Lintang Dian Saraswati (Media Penelitian dan Pengembangan Kesehatan, 2021)
Measles rubella (MR) is a highly contagious disease, rubella causes miscarriage or baby-ies born with congenital defects in the first trimester of pregnancy. The Ministry of Health recommends 95% of the population against rubella measles through the Measles Rubella Immunization Program. However, there is still MR immunization coverage below 95%, in the Magelang City. Public Health Center has coverage of MR was 83.56% and Magelang Selatan was 89.14%. The purpose of the study was to analyse the factors associated with rejection of MR immunization. Study design using cross sectional. 120 samples of parents from elementary, junior high school, and SLB were selected in Magelang Utara sub-district with simple random sampling. The variables that had a statistical- relationship with the status of immunization refusal of Measles Rubella (p < 0.05) were type of work, history of measles,level of knowledge, attitudes of student’s parent attitudes (p = 0,0001), perceived vulnerability (p = 0,0001), perceived severity (p = 0,0001), perceived benefits and barriers, environment support, family support, and school support. So that parents with poor knowledge have a 18.355 times greater chance of rejecting Measles rubella Immunization. Abstrak Measles rubella (MR) merupakan penyakit yang sangat menular, rubela mengakibatkan keguguran atau bayi lahir dengan cacat bawaan pada kehamilan trimester I. Kementerian Kesehatan menganjurkan kekebalan populasi terhadap penyakit campak rubela sebesar 95% melalui Program Imunisasi Measles Rubella. Cakupan MR di Kota Magelang Provinsi Jawa Tengah masih < 95%. Puskesmas Magelang Utara mempunyai cakupan MR sebesar 83,56%, dan Magelang Selatan sebesar 89,14%. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang berhubungan dengan penolakan imunisasi MR. Desain studi menggunakan potong lintang. Terpilih 120 sampel wali murid dari SD, SMP, dan SLB di Kecamatan Magelang Utara dengan simple random sampling. Variabel yang memiliki hubungan secara statistik dengan status penolakan imunisasi Measles Rubella adalah jenis pekerjaan, riwayat campak, tingkat pengetahuan, sikap wali murid (p=0,0001), persepsi kerentanan (p=0,0001), persepsi keparahan (p=0,0001), persepsi manfaat dan hambatan, dukungan lingkungan, dukungan keluarga, dan dukungan sekolah. Wali murid dengan pengetahuan kurang baik memiliki peluang 18,355 kali lebih besar untuk menolak Imunisasi MR.